Removal of a catheter kinked in the radial artery by anchoring the distal part of the catheter with a needle via transcutaneous approach - Yakup Balaban; Ali Hıdır Kayışoğlu; Altuğ Tokatlı; Aykut Tantan (KARE Publishing, 2018)
Presently described is a case in which a catheter became twisted in the radial artery during coronary angiography and was removed after stretching it with an external needle tip inserted into the brachial artery. A 77-year-old male patient had undergone coronary artery bypass surgery 10 years earlier and implantation of a permanent pacemaker 2 years prior. He had presented with typical angina and a regional wall motion defect had been observed on echocardiography. Coronary angiography was scheduled. A 5-F sheath (Terumo Corp., Tokyo, Japan) was inserted, and angiography via the right radial artery was initiated. Soon after, the 5-F diagnostic catheter became twisted due to subclavian artery tortuosity. The fold in the catheter could not be flattened with 0.038-mm or 0.035-mm guidewires or rotation movements. With scopy assistance, a 21-gauge, 40-mm, green needle was inserted percutaneously into the catheter through the brachial artery. So, the catheter was stretched and the kink could then be corrected and the catheter was removed from the sheath. Subsequent Images revealed no trauma or deformity to the brachial or radial arteries. It was not possible to straighten the fold until the distal portion of the catheter was fixed in place and stretched. A catheter can be transdermally anchored with a needle if it becomes kinked in the upper extremity vessels. This is a simple and reliable method that is a traumatic.